Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Regional Emergence of Water‐Related Browning in a Greening World - Rene Orth; Jasper M. C. Denissen; Josephin Kroll; Sungmin O; Ana Bastos; Wantong Li; Diego G. Miralles; Melissa Ruiz‐Vásquez; Anne J. Hoek van Dijke; Andrew F. Feldman; Mirco Migliavacca; Lan Wang‐Erlandsson; et al. (Global Change Biology, 2025)
The Earth is greening in many regions under elevated atmospheric CO 2 concentrations, along with increasing temperature and land use changes. However, despite the continued rise in CO 2 , greening has stagnated or even reversed in some regions, suggesting a reduced capacity of the land surface to act as a carbon sink. Here, we show that declining water availability and rising atmospheric water demand have coincided with regional browning trends over recent decades in some tropical regions that have historically acted as prominent carbon sinks. A regression analysis considering a balanced set of water‐ and energy‐related variables alongside land cover change and climate extremes confirms that both water availability and atmospheric water demand are important contributors to inter‐annual variability in Leaf Area Index (LAI) there. Earth system models mostly reproduce the observed spatial extent of browning and concurrent related coinciding water changes in the multi‐model mean, but results from individual models differ strongly. Our findings provide a new constraint for related model development and highlight the need for enhanced monitoring and consideration of observation‐based water availability trends as an emerging driver of vegetation in future analyses and model development.

Coupled Dynamics of Fecal Indicator Bacteria in Sandy Sediments and the Water Column: a 3-Year High-Frequency Study at a Pennsylvania Creek - Y. Pachepsky; M. D. Harriger; C Panko Graff; M. D. Stocker; J. E. Smith; J. M. Slifka (Water, Air, & Soil Pollution, 2023)

Intraseasonal variation of phycocyanin concentrations and environmental covariates in two agricultural irrigation ponds in Maryland, USA - J. E. Smith; M. D. Stocker; J. L. Wolny; R. L. Hill; Y. A. Pachepsky (Environmental Monitoring and Assessment, 2020)

Manure Consistency and Weathering Affect the Removal of Fecal Indicator Bacteria from Grass-Covered Soil - M. D. Stocker; R. L. Hill; Y. A. Pachepsky (Water, Air, & Soil Pollution, 2020)

Functional Evaluation of Three Manure-Borne Indicator Bacteria Release Models with Multiyear Field Experiment Data - M. Stocker; A. Yakirevich; A. Guber; G. Martinez; R. Blaustein; G. Whelan; D. Goodrich; D. Shelton; Y. Pachepsky (Water, Air, & Soil Pollution, 2018)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Thief workers and variation in nestmate recognition behavior in a ponerine ant, Ectatomma ruidum - M. D. Breed; T. P. McGlynn; E. M. Stocker; A. N. Klein (Insectes Sociaux, 1999)